Venoms of New World Vinesnakes (Oxybelis aeneus and O. fulgidus). (30th January 2021) - Heyborne, William H.; Mackessy, Stephen P.
Abstract: Species of Oxybelis are extremely elongate arboreal snakes that are broadly distributed in the Americas, from extreme southeastern Arizona (USA) to central South America. Primarily feeding on lizards and birds, Oxybelis venoms are poorly known in general, but a prominent taxon-specific three-finger toxin (fulgimotoxin) was isolated from and is a prominent component of O. fulgidus venom; a homolog is also present in O. aeneus venom. As part of ongoing characterization of venoms from rear-fanged snakes, we describe here the composition of two broadly distributed species, O. aeneus and O. fulgidus . Venom proteomes were of very low complexity, and four protein families (LAAO, PIII SVMP, CRiSP and 3FTx) account for more than 90% of total protein composition. Venoms from both species are moderately toxic to mice and to Hemidactylus geckos, but they are nearly an order of magnitude more toxic to Anolis lizards (a native prey species). These results reflect a trend in colubrid venom composition that is becoming increasingly more common: the presence of taxon-specific toxins, specifically three-finger toxins, preferentially targeting lizards and/or birds. Graphical abstract: Image 1 Highlights: Oxybelis range from southern Arizona to central South America. Venoms of O. aeneus and O. fulgidus show low complexity but contain three-finger toxins. 1-D SDS-PAGE and MALDI-TOF MS demonstrated greater complexity of 3FTx toxins in O. aeneus venoms. Both venoms are highly toxic toward Anolis lizards, commonly taken as prey, and much less toxic to mammals. Presence of taxon-specific toxins appears to be relatively common among venoms of rear-fanged colubrid snakes.